PENATAAN LEMBAGA KEMASYARAKATAN DESA DI KECAMATAN TAMBANG TAHUN 2010 - 2015 - Krisnawati, Cici; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the implementation of rural development needed social institutions are able to mobilize the community to be able to participate in implementing rural development as well as the administration of rural development. Institute for Community Empowerment (LPMD) referred responsible to assist the Government of the village and is a partner in empowering the village community. However, a phenomenon that occurs is still visible today is the Community Institutions in Kampar regency is still composed and recorded properly so that the social institutions that have been established less have a role and contribute the maximum in the community. The purpose of this study was to determine the arrangement of Community Institutions in the Kecamatan Tambang of Mine Years 2010-2015 and to identify constraints in the arrangement of Community Institutions in the Kecamatan Tambang of Mine Years 2010-2015.This research was conducted in the Kecamatan Tambang, Kabupaten Kampar, Riau Province. The study is based on the importance of Community Institutions Structuring village in the district of Kabupaten Kampar, Province Riau. Data used in this study was composed of primary data and secondary data with the number of informants as many as 7 people. Intake of informants by using purposive sampling technique. The analysis of the data used in this study is a qualitative descriptive way than that obtained from direct observations on the object of government policy in the Kampar Regency Village Community Institutions structuring of research and interviews by plugging qualitatively. Based on the results of research conducted by the author can be concluded that the arrangement of the Village Community Institutions in the Kabupaten Kampar Year 2010-2015 conducted in the following manner: 1) Socialization Program and Activities, 2) Strengthening the Institutional Capacity, 3) Capacity Enhancement (Capacity Building), 4) Capacity Management, 5) Assistance and 6) control and supervision. The constraints experienced in the Community Institutions Structuring village in Kabupaten Kampar Regency Year 2010-2015 is influenced by three (3) factors are as follows: 1) The lack of awareness and community participation, 2) lack of network development among fellow agencies, and 3) lack of supervision.Keywords: Arrangement, Rural Community Institutions